A strategy to enhance the distribution systems recoverability via the simultaneous coordination of planning actions and operational resources - Home-Ortiz, Juan M. [UNESP]; Melgar-Dominguez, Ozy D. [UNESP]; Javadi, Mohammad Sadegh; Gough, Matthew B.; Mantovani, José Roberto Sanches [UNESP]; Catalão, João P.S. (Elsevier, 2023)
This paper presents a planning and operational strategy to improve the recoverability of distribution systems (DSs) to deal with a set of possible line fault scenarios. The strategy simultaneously optimizes the allocation of dispatchable distributed generation (DG) units while coordinating a dynamic restoration process based on a radial topology reconfiguration, an islanding operation, a demand response program, and the pre-positioning and dispatch of mobile emergency storage units. The uncertainty and variability associated with solar irradiation and demand are captured via a multi-period formulation based on a stochastic mixed-integer linear programming model. The objective function of this model minimizes the investment cost of new dispatchable DG units and the amount of energy shedding within the system. Simulations are performed on adapted 33-node and 53-node test systems to validate the proposed strategy under four different test conditions, numerical results reveal the advantages of simultaneously solving the planning and operational stages to improve the recoverability of the system.
Keywords: Demand response; Distributed generation allocation; Distribution systems; Mobile emergency storage; Resilience; Restoration